Ratiometric Fluorescent Probe Based on FRET for Imaging Hg²⁺ Ions in Living Cells - Zhang, Xiaolin; Xiao, Yi; Qian, Xuhong (Angewandte Chemie International Edition, 2008)
Mercury rising: A FRET‐based ratiometric probe (see picture; FRET=fluorescence resonance energy transfer) can selectively detect Hg2+ ions on the parts‐per‐billion scale under physiological conditions. The probe undergoes a clear Hg2+‐induced change in the intensity ratio of the two well‐separated and equally intense emission bands of dipyrrometheneboron difluoride and rhodamine. Experiments show that the probe can be used in living cells.